Cardiovascular disease risk factors and markers of oxidative stress and DNA damage in leprosy patients in Southern Nigeria. - Iya Eze Bassey; Inyeneobong Ernest Inyang; Uwem Okon Akpan; Idongesit Kokoabasi Paul Isong; Bassey Edward Icha; Victoria Micheal Ayawan; Racheal Ekanem Peter; Hopefaith Adode Itita; Prince Ukam Odumusor; Eyoanwan Graziani Ekanem; Okon Ekwerre Essien (Public Library of Science (PLoS), 2020)
Leprosy reduces quality of life of affected persons. Oxidative stress caused by reactive oxygen species may play a vital role in the pathogenesis of leprosy. This study evaluated anthropometric indices, fasting plasma glucose (FPG), lipid profile, total antioxidant capacity (TAC), total plasma peroxide (TPP), oxidative stress index (OSI), malondialdehyde (MDA), glutathione (GSH) and 8-hydroxy-2-deoxyguanosine (8-OHdg) in leprosy patients. Sixty test participants of both genders, aged 18-65years and diagnosed of multibacillary leprosy and 30 apparently healthy controls were consecutively recruited for this study. The test participants comprised of 30 patients on multidrug therapy (MDT) and 30 patients relieved from therapy (RFT). Body mass index (BMI), Waist-hip ratio (WHR), FPG, lipid profile, TAC, TPP, OSI, MDA, GSH and 8-OHdg were determined using appropriate methods. Data were analyzed using Analysis of variance; p<0.05 was considered statistically significant. The MDT group had significantly lower BMI (p = 0.0001), Total cholesterol (p = 0.001), HDL-C (p = 0.019), LDL-C (p = 0.005), TAC (p = 0.0001) and higher TPP (p = 0.001), MDA (p = 0.0001), OSI (p = 0.005) and 8-OHdg (p = 0.035) compared to the controls. The RFT group had significantly lower BMI (p = 0.001) Total cholesterol (0.0001), HDL-C (p = 0.006) LDL-C (p = 0.0001), TAC (p = 0.001) and higher WHR (p = 0.010), VLDL-C (p = 0.035), TG (p = 0.023) Atherogenic index of plasma (p = 0.0001) and TPP (p = 0.001), MDA (p = 0.0001) compared to the control group. GSH levels correlated negatively with duration of treatment (r = -0.401, p = 0.028). This study has shown that there is oxidative stress in multibacillary leprosy patients irrespective of drug treatment status. This study also shows that leprosy patients relieved from treatment may be susceptible to cardiovascular events. Antioxidants supplementation may be beneficial in the treatment of leprosy and clinical follow up on patients relieved from treatment may also be necessary to monitor health status and prevent development of cardiovascular events.